Integrated simultaneous nitrification/denitrification and comammox consortia as efficient biocatalysts enhance treatment of domestic wastewater in different up-flow bioelectrochemical reactors. (November 2021) - Yang, Nuan; Zhan, Guoqiang; Luo, Huiqin; Xiong, Xia; Li, Daping
Graphical abstract: Highlights: The domestic wastewater was successfully treated by UBERs with different AEBs. Activated functional biofilms were constructed in different anodes and AEBs. 3D bioelectrodes dominated by abundant NRB and EAB were acclimated. Integration of SND and comammox could enhance domestic wastewater treatment. FAPROTAX prediction was used to evaluate the microbial functions. Abstract: Simultaneous nitrification/denitrification (SND) can efficiently deplete NH4 + by using air-exposed biocathode (AEB) in bioelectrochemical reactors. However, the fluctuation of wastewater adversely affects the functional biofilms and therefore the performance. In this work, four up-flow bioelectrochemical reactors (UBERs) with some novel inocula were investigated to improve domestic wastewater treatment. The UBERs exhibited favorable removal of chemical oxygen demand (COD, 95%), NH4 + -N (99%), and total nitrogen (TN, 99%). The maximum of current (2.7 A/m 3 ), power density (136 mW/m 3 ) and coulombic efficiency (20.5%) were obtained. Cyclic voltammetry analysis showed all the electrodes were of diversified catalytic reactions. Illumina pyrosequencing showed the predominant Ignavibacterium, Thauera, Nitrosomonas, Geminicoccus and Nitrospira were in all electrodes, contributing functional biofilms performing SND, comammox, and bioelectrochemical reactions. FAPROTAX analysis confirmed twenty-one functional groups with obvious changes related to chemoheterotrophy, respiration/oxidation/denitrification of nitrite and nitrate. Comfortingly, such novel diversified consortia in UBERs enhance the microbial metabolisms to treat domestic wastewater.